The Evolution of Strategic Sophistication. - Robalino, Nikolaus; Robson, Arthur (American Economic Review, 2016)
This paper investigates the evolutionary foundation for our ability to attribute preferences to others, an ability that is central to conventional game theory. We argue here that learning others' preferences allows individuals to efficiently modify their behavior in strategic environments with a persistent element of novelty. Agents with the ability to learn have a sharp, unambiguous advantage over those who are less sophisticated because the former agents extrapolate to novel circumstances information about opponents' preferences that was learned previously. This advantage holds even with a suitably small cost to reflect the additional cognitive complexity involved. (JEL C73, D11, D83)